Exhibition Reviews. Issue 2 (1st March 2015) - McIntyre, Ellen; Miller, Janice
Fashion Rules: Dress from the Collections of HM The Queen, Princess Margaret and Diana, Princess of Wales, Kensington Palace, London, 4 July 2013–Summer 2015David Bowie is inside…David Bowie Is, Victoria and Albert Museum, London, 23 March–11 August 2013